2020
DOI: 10.5395/rde.2020.45.e49
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective clinical and radiographic evaluation of restored endodontically treated teeth

Abstract: Objectives: The aim of this study was to perform a clinical and radiographic analysis of endodontically treated teeth (ETT) restored with cast metal posts (CMPs) or prefabricated glass fiber posts (GFPs) and crowns. Materials and Methods: Fifty ETT were restored with 25 CMPs and 25 GFPs at a private dental clinic between 2001 and 2016. The restorations consisted of 12 all-ceramic crowns, 31 metalceramic crowns, and 7 composite resin crowns. Demographic data, type of teeth, type of post-and-core system, time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
1
0
2
Order By: Relevance
“…The lower bond strength values were recorded when small sized posts were used in oversized post spaces, as in space 1 (600 μm) and space 2 (350–400 μm) (size 4 and size 5 posts luted in post space prepared with size 6 Parapost drill). These findings are similar to previous studies, which showed that the debonding of posts occurs when cement film thickness is increased [ 12 , 14 ]. It was proposed from the studies that when the cement layer is thinner, there will be less micro-porosities and polymerization stress, leading to higher retentive bond strength [ 14 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lower bond strength values were recorded when small sized posts were used in oversized post spaces, as in space 1 (600 μm) and space 2 (350–400 μm) (size 4 and size 5 posts luted in post space prepared with size 6 Parapost drill). These findings are similar to previous studies, which showed that the debonding of posts occurs when cement film thickness is increased [ 12 , 14 ]. It was proposed from the studies that when the cement layer is thinner, there will be less micro-porosities and polymerization stress, leading to higher retentive bond strength [ 14 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Little information is available on the role of cement film thickness and its effect on the retention of posts [ 6 , 9 , 10 , 11 ]. Previous clinical retrospective studies have demonstrated that the debonding of posts occurs when luting cement film thickness is increased [ 12 , 13 , 14 ]. However, there is no consensus on the ideal thickness of the luting cement to improve the retentive bond strength of posts in endodontically treated teeth [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo realizado por Garcia et al (2020) foi feita uma análise clínica e radiográfica de dentes tratados endodonticamente restaurados com núcleos de metal fundido ou pinos pré-fabricados de fibra de vidro. Para isso, 50 dentes foram restaurados, sendo com 25 núcleo metálico fundido e 25 com pinos de fibra de vidro em uma clínica odontológica privada entre 2001 e 2016.…”
Section: Resultsunclassified
“…De acordo com os estudos avaliados, observou-se que, em geral, os pinos de fibra de vidro apresentaram desempenho similar aos núcleos metálicos fundidos, sendo considerados uma alternativa viável e eficaz para a restauração de dentes tratados endodonticamente, especialmente em áreas anteriores, nas quais há maiores exigências estéticas (GIOVANI et al, 2009;FIGUEIREDO et al, 2015;MARCHIONATTI et al, 2017;CLOET et al, 2017;GARCIA et al, 2020;SARKIS-ONOFRE et al, 2020). Apesar de serem relacionados a procedimentos de maior custo, os pinos de fibra de vidro devem ser levados em consideração tendo em vista suas vantagens estéticas e o bom desempenho em longo prazo (SCHWENDICKE et al, 2020).…”
Section: Resultsunclassified